Lexical semantics for terminology an introduction - L'Homme, Marie-Claude (John Benjamins Publishing Company, 2019)
Lexical Semantics for Terminology: An introduction' explores the interconnections between lexical semantics and terminology. More specifically, it shows how principles borrowed from lexico-semantic frameworks and methodologies derived from them can help understand terms and describe them in resources. It also explains how lexical analysis complements perspectives entirely focused on knowledge. Issues such as term identification, meaning, polysemy, relations between terms, and equivalence are discussed thoroughly and illustrated with various examples taken from different fields of knowledge.0This book is intended for readers who are interested in words and need to handle specialized terms as part of their activities, i.e. terminologists, translators, lexicographers, corpus linguists. A background in terminology or lexical semantics is not required since all notions are defined and explained. This book should complement other textbooks on terminology that do not focus on lexical semantics per se.